Regeneration of the surface precipitation pollution in inertial purifier - Шевчук, В.С.; Пузік, С.О.; Манзій, В.С.; Закревський, В.О. (Proceedings of National Aviation University (archive), 2008)
The analytical studies results of regeneration of precipitated surfaces of accelerative type cleaners are given. Proposed method allows to appreciate the influence both sliding friction and rolling friction of discrete pollution parts.